Decentralization, Budget Participation and Managerial Work Achievements - Urika Urika (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Research on decentralization and budget participation on managerial performance lately is a field of research that many have debates, thus attracting the interest of researchers to conduct further studies of the influence. The population in this study is the manager of the Company's manufacturing industry with sampling purposive sampling techniques. The analysis tool to test the hypothesis using simple regression analysis.Research generates Decentralization positive and significant impact on Managerial Performance. meaning that the higher the decentralization of the motivation of the manager with the unmet need for self-actualization. Participation Budget negative and significant effect on Managerial Performance. This means that in the preparation of the budget involved some employees may of them have properties that are less concerned about the budget so that less cooperative.